Drivers of roe deer use in fragmented forest landscapes; implications for current and future management in the context of policy driven forest expansion - Saudamini Venkatesan; Benjamin M. Marshall; Mark S. Greener; Anna Kinghorn; Isla Sligo-Young; Richard Hassall; Robin Gill; Ben McKeown; Jeanette Hall; Roman Biek; Lucy Gilbert; Thomas A. Morrison; et al. (Forest Ecology and Management, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Cellulosic biorefinery siting and biomass supply logistics incorporating biomass and moisture dynamics in the crop season and during storage - Yubin Yang; Lloyd T. Wilson; Jing Wang; Fugen Dou; Tanumoy Bera; Joseph E. Knoll; John L. Jifon; Dennis C. Odero; Brian S. Baldwin; William L. Rooney; Hamid Araji; Jesse I. Morrison; et al. (Biomass and Bioenergy, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Insecticidal effect of deltamethrin, pyrethrin, and spinosad on metal and concrete surfaces on six species of stored product insects - Deanna S. Scheff; Codi Mueller; Alexus Delaney; William R. Morrison (Journal of Stored Products Research, 2026)

Population genetics of the endangered narrowly endemic Island Marble butterfly (Euchloe ausonides insulanus) - Kara S. Jones; Aaron W. Aunins; Colleen C. Young; Robin L. Johnson; Cheryl L. Morrison (Conservation Genetics, 2026)

Accuracy of SeaHawk-HawkEye Ocean color CubeSat remote sensing reflectance products in globally distributed aquatic sites - Srinivas Kolluru; Sara Rivero-Calle; Philip J. Bresnahan; Susanne Kratzer; Timothy S. Moore; Thomas Schroeder; Sean Bailey; Alan Holmes; John M. Morrison; Gene F. Feldman; Liang Hong; Hiroto Higa; et al. (Remote Sensing of Environment, 2026)

Purification techniques for oxygen isotope analysis of inorganic phosphate across environmental matrices: A cross-discipline review - Shin-Ah Lee; Spencer R. Moller; Amanda R. Chappel; Sydney Riemer; Gareema Dhiman; Ruth Blake; Elise S. Morrison (Journal of Environmental Management, 2026)

Ambient environmental conditions and active outdoor play in the context of climate change: A systematic review and meta-synthesis - Eun-Young Lee; Seiyeong Park; Yeong-Bae Kim; Henry Liu; Priya Mistry; Kevin Nguyen; Yeonjae Oh; Maeghan E. James; Steven Lâm; Louise de Lannoy; Richard Larouche; Taru Manyanga; et al. (Environmental Research, 2025)

The U.S. Ecosystem‐Based Fisheries Management Policy and Road Map: Assessing Progress and Applying Lessons Learned - Chris J. Harvey; Yvonne L. deReynier; Wendy E. Morrison; Jennifer L. Cudney; Dorothy M. Dick; Travis Ford; Karla Gore; Jamison M. Gove; Elliott L. Hazen; Jerome M. Hermsen; Keith Kamikawa; Mandy Karnauskas; et al. (Fish and Fisheries, 2025)
The need for ecosystem‐based fisheries management (EBFM) is growing more urgent as environmental changes, species shifts, new ocean uses, and other factors force oceans toward novel states. In the United States, the National Oceanic and Atmospheric Administration's National Marine Fisheries Service (NOAA Fisheries) developed an EBFM Policy in 2016, accompanied by a Road Map of 49 action items, to support marine ecosystem‐based management and conservation of fisheries, habitats, and protected species under U.S. federal jurisdiction. In 2024, NOAA Fisheries updated its EBFM Policy and Road Map and formed a team of science and policy experts to review progress and derive lessons learned during the first Road Map iteration. Four key lessons emerged: (1) progress toward EBFM in the U.S. has been substantial; (2) greater coordination could further enhance progress; (3) more effort is required to link science to management activities; and (4) human dimensions need greater integration throughout EBFM implementation. Enabling factors for progress on the Road Map included: champions at both the leadership and staff levels; use of participatory processes; motivation driven by ecosystem shocks and threats; and leveraging existing processes and frameworks. The updated EBFM Road Map supports historic and ongoing efforts to implement U.S. laws through improved coordination, integration, and knowledge exchange and can help to address many urgent challenges facing U.S. marine fisheries, habitats, and protected resources.

Experimental Challenge of Chinook Salmon ( Oncorhynchus tshawytscha ) With Tenacibaculum maritimum and Tenacibaculum dicentrarchi Fulfils Koch's Postulates - Karthiga Kumanan; Jeremy Carson; Ryan B. J. Hunter; Anne Rolton; Ulla von Ammon; Chaya Bandaranayake; Connie Angelucci; Richard N. Morrison; Seumas P. Walker; Jane E. Symonds; Kate S. Hutson (Journal of Fish Diseases, 2025)
The bacterial skin disease tenacibaculosis, caused by Tenacibaculum species, affects numerous economically important marine fish, including salmonids. This study reports the ability of three Tenacibaculum maritimum strains, belonging to different molecular O‐AGC types, and a single Tenacibaculum dicentrarchi strain to induce tenacibaculosis in farmed Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792) in Aotearoa New Zealand. Naïve Chinook salmon were exposed to T. maritimum (2 × 10 8 cells/mL) and T. dicentrarchi (2 × 10 7 cells/mL) by immersion using natural seawater. Clinical signs of tenacibaculosis were apparent in all T. maritimum strains used in the challenged fish. Of these, 100% of the fish challenged with O‐AGC Type 2‐1 and Type 3‐2 strains became moribund, whereas only 60% of the O‐AGC Type 3‐0 challenged fish became moribund. Fish exposed to T. dicentrarchi showed more severe symptoms, exposing musculature in 51% of the challenged population, with 28% of fish becoming moribund. Gross pathological signs of fin rot, scale loss, skin ulcers and haemorrhagic skin spots were observed for both Tenacibaculum species and were consistent with those observed on farmed fish. Pure T. maritimum and T. dicentrarchi cultures were reisolated from epidermal damage of challenged fish. Tenacibaculum species was not isolated from the anterior kidney of affected fish, which indicates no systemic infection in Chinook salmon.

Quantifying the influence of climate change on pesticide risks in drinking water - J. Harmon O'Driscoll; M.G. Healy; A. Siggins; J. McGinley; E. O'Brien; J. Wang; P. Holloway; P.-E. Mellander; L. Morrison; S. Scannell; P.C. Ryan (Science of The Total Environment, 2025)

Experimental Measurement and Mathematical Quantification of Fixed-Charged Density in Rat and Pig Brain Tissue - Delin Zeng; Andrew V. Basilio; Leanne A. Pichay; Gerard A. Ateshian; Olivia S. Hansen; Alexander Romanov; Barclay Morrison (Annals of Biomedical Engineering, 2025)

Corrigendum to “Lead exposure by E-waste disposal and recycling in Agbogbloshie, Ghana” [Int. J. Hyg. Environ. Health 259C (2024) 114375] - P. Püschel; K.M. Agbeko; A.A. Amoabeng-Nti; J. Arko-Mensah; J. Bertram; J.N. Fobil; S. Waldschmidt; K. Löhndorf; T. Schettgen; M. Lakemeyer; A. Morrison; T. Küpper (International Journal of Hygiene and Environmental Health, 2025)

Evidence of eastern rockhopper penguin feeding on a key commercial arrow squid species - Hugo R. Guímaro; David R. Thompson; Kyle W. Morrison; Joana Fragão; Ricardo S. Matias; José C. Xavier (Polar Biology, 2025)
Cephalopods are crucial to the Southern Ocean ecosystem, connecting top predators with mid-trophic organisms, yet their ecology in the Pacific sector is not well understood. This research used stable isotope analysis to explore the habitat and trophic ecology of cephalopods found in the diet of eastern rockhopper penguins ( Eudyptes chrysocome filholi ) around Campbell Island, a New Zealand sub-Antarctic island. Eastern rockhopper penguins were used as biologic samplers, revealing some differences in cephalopod diversity and ecology between two breeding seasons—1986–87 and 2012–13—, and the squid Nototodarus sloanii , a commercially valuable species, was described for the first time in the 2012–13 season. Stable isotope values ( δ 13 C and δ 15 N) for the squid species Moroteuthopsis ingens were consistent between seasons, indicating ecological stability, whereas the octopod species Octopus campbelli showed changes, suggesting shifts in habitat and feeding. Warmer oceanic temperatures in 2012–13 may have facilitated the emergence of N. sloanii on the diet of the eastern rockhopper penguins. These findings highlight potential changes in cephalopod biodiversity in the Pacific sector of the Southern Ocean, emphasizing the need for further research on ecological dynamics of this region.

Fate of a toxic Microcystis aeruginosa bloom introduced into a subtropical estuary from a flow-managed canal and management implications - Edward J. Phlips; Susan Badylak; Eric C. Milbrandt; Benjamin Stelling; Mauricio Arias; Cassondra Armstrong; Thomas Behlmer; Amanda Chappel; Amanda Foss; David Kaplan; Leslie Landauer; Peter Landauer; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Influence of regulated water discharges on phytoplankton composition and biomass in a subtropical canal - Susan Badylak; Edward J. Phlips; Eric C. Milbrandt; Elise S. Morrison; Benjamin D. Stelling; Shin-Ah Lee; Thomas A. Frankovich; David Kaplan (Journal of Environmental Management, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Floating debris and organisms can raft to Antarctic coasts from all major Southern Hemisphere landmasses - Hannah R. S. Dawson; Matthew H. England; Adele K. Morrison; Veronica Tamsitt; Ceridwen I. Fraser (Global Change Biology, 2024)
Antarctica's unique marine ecosystems are threatened by the arrival of non‐native marine species on rafting ocean objects. The harsh environmental conditions in Antarctica prevent the establishment of many such species, but warming around the continent and the opening up of ice‐free regions may already be reducing these barriers. Although recent genomic work has revealed that rafts—potentially carrying diverse coastal passengers—reach Antarctica from sub‐Antarctic islands, Antarctica's vulnerability to incursions from Southern Hemisphere continents remains unknown. Here we use 0.1° global ocean model simulations to explore whether drift connections exist between more northern, temperate landmasses and the Antarctic coastline. We show that passively floating objects can drift to Antarctica not only from sub‐Antarctic islands, but also from continental locations north of the Subtropical Front including Australia, South Africa, South America and Zealandia. We find that the Antarctic Peninsula is the region at highest risk for non‐native species introductions arriving by natural oceanic dispersal, highlighting the vulnerability of this region, which is also at risk from introductions via ship traffic and rapid warming. The widespread connections with sub‐Antarctic and temperate landmasses, combined with an increasing abundance of marine anthropogenic rafting vectors, poses a growing risk to Antarctic marine ecosystems, especially as environmental conditions around Antarctica are projected to become more suitable for non‐native species in the future.

Female mountain gorillas form enduring social relationships - Riley N. Derby; Winnie Eckardt; Tara S. Stoinski; Robin E. Morrison; Aaron A. Sandel (Animal Behaviour, 2024)

Lead exposure by E-waste disposal and recycling in Agbogbloshie, Ghana - P. Püschel; K.M. Agbeko; A.A. Amoabeng-Nti; J. Arko-Mensah; J. Bertram; J.N. Fobil; S. Waldschmidt; K. Löhndorf; T. Schettgen; M. Lakemeyer; A. Morrison; T. Küpper (International Journal of Hygiene and Environmental Health, 2024)

Influence of the Keystone Grazer, Sesarma reticulatum, on the Hydrology and Organic Matter Cycling in Salt Marshes of the Southeastern USA - Elise S. Morrison; Thomas S. Bianchi; William F. Kenney; Mark Brenner; Kimberly Prince; Sydney Williams; Collin Ortals; Orlando Cordero; Sinéad M. Crotty; Christine Angelini (Estuaries and Coasts, 2024)
In salt marshes of the Southeastern USA, purple marsh crabs ( Sesarma reticulatum ), hereafter Sesarma , aggregate in grazing and burrowing fronts at the heads of tidal creeks, accelerating creek incision into marsh platforms. We explored the effects of this keystone grazer and sediment engineer on salt marsh sediment accumulation, hydrology, and carbon (C) and nitrogen (N) turnover using radionuclides ( 210 Pb and 7 Be), total hydrolyzable amino acids (THAA), and C and N stable isotopes (δ 13 C and δ 15 N) in sediment from paired Sesarma -grazed and un-grazed creeks. Sesarma -grazed-creek sediments exhibited greater bioturbation and tidal inundation compared to sediments in un-grazed creeks, as indicated by larger 210 Pb and 7 Be inventories. Total organic carbon (TOC) to total nitrogen (TN) weight ratios (C:N) were higher and δ 15 N values were lower in grazed-creek sediments than in un-grazed-creek sediments, suggesting Sesarma remove and assimilate N in their tissues, and excrete N with lower δ 15 N values into sediments. In support of this inference, the percent total carbon (TC) and percent TOC declined by nearly half, percent TN decreased by ~ 80%, and the C:N ratio exhibited a ~ threefold increase between Sesarma fore-gut and hind-gut contents. An estimated 91% of Sesarma ’s diet was derived from Spartina alterniflora, the region’s dominant salt marsh plant. We found that, as Sesarma grazing fronts progress across marsh landscapes, they enhance the decay of Spartina- derived organic matter and prolong marsh tidal inundation. These findings highlight the need to better account for the effects of keystone grazers and sediment engineers, like Sesarma , in estimates of the stability and size of blue C stores in coastal wetlands.

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

Region-Dependent Mechanical Properties of Human Brain Tissue Under Large Deformations Using Inverse Finite Element Modeling - Andrew V. Basilio; Delin Zeng; Leanne A. Pichay; Steve A. Maas; Sowmya N. Sundaresh; John D. Finan; Benjamin S. Elkin; Guy M. McKhann; Gerard A. Ateshian; Barclay Morrison (Annals of Biomedical Engineering, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Serological and molecular typing of Tenacibaculum maritimum from New Zealand farmed salmon, Oncorhynchus tshawytscha - Karthiga Kumanan; Lizenn Delisle; Connie Angelucci; Ryan B.J. Hunter; Oleksandra Rudenko; Jeremy Carson; Richard N. Morrison; Andrew C. Barnes; Kate S. Hutson (Aquaculture, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Algal blooms in a river-dominated estuary and nearshore region of Florida, USA: the influence of regulated discharges from water control structures on hydrologic and nutrient conditions - E. J. Phlips; S. Badylak; A. L. Mathews; E. C. Milbrandt; L. R. Montefiore; E. S. Morrison; N. Nelson; B. Stelling (Hydrobiologia, 2023)
Flow-regulated discharges of water from control structures into estuaries result in hydrologic and water chemistry conditions that impact spatial and temporal variability in the structure and biomass of phytoplankton communities, including the potential for harmful algal blooms (HABs). The relationships between regulated Caloosahatchee River (i.e., C-43 Canal) discharges and phytoplankton communities in the Caloosahatchee Estuary and adjacent nearshore regions on the southwest coast of Florida were investigated during two study periods, 2009–2010 and 2018–2019. During periods of low to moderate discharge rates, when mesohaline conditions predominated in the estuary, and water residence times were comparatively long, major blooms of the HAB dinoflagellate species Akashiwo sanguinea were observed in the estuary. Periods of high discharge were characterized by comparatively low phytoplankton biomass in the estuary and greater influence of a wide range of freshwater taxa in the upper reaches. By contrast, intense blooms of the toxic dinoflagellate Karenia brevis in the nearshore region outside of the estuary were observed during high discharge periods in 2018–2019. The latter events were significantly associated with elevated levels of nitrogen in the estuary compared to lower average concentrations in the 2009–2010 study period. The relationships observed in this study provide insights into the importance of managing regulated discharge regimes to minimize adverse impacts of HABs on the health of the estuary and related coastal environments.

Phytohormonal impacts on fatty acid profiles in Chlorella vulgaris Beijerinck: endogenous identification and exogenous application of cytokinins and abscisic acid - Kira Ramphal; Ainsely Lewis; Natasha A. Trzaskalski; Anna Kisiala; Erin N. Morrison; Suresh S. Narine; R. J. Neil Emery (Journal of Applied Phycology, 2023)

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Controls on the composition of dissolved organic matter in treatment wetland source waters of South Florida, USA - Joao Henrique F. Amaral; Jacob R. Gaddy; Thomas S. Bianchi; Todd Z. Osborne; Susan Newman; Jacob Dombrowski; Elise S. Morrison (Ecological Engineering, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Current State and Opportunities with Long-acting Injectables: Industry Perspectives from the Innovation and Quality Consortium “Long-Acting Injectables” Working Group - Andrea Bauer; Philippe Berben; Sudhir S. Chakravarthi; Sayantan Chattorraj; Ashish Garg; Betty Gourdon; Tycho Heimbach; Ye Huang; Christopher Morrison; Deepak Mundhra; Ramesh Palaparthy; Pratik Saha; et al. (Pharmaceutical Research, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Correction: Circulatory system disease mortality and occupational exposure to radon progeny in the cohort of Newfoundland Fluorspar Miners between 1950 and 2016 - Paul J. Villeneuve; Howard I. Morrison; Karena Volesky; Rachel S. D. Lane (International Archives of Occupational and Environmental Health, 2023)

Circulatory system disease mortality and occupational exposure to radon progeny in the cohort of Newfoundland Fluorspar Miners between 1950 and 2016 - Paul J. Villeneuve; Howard I. Morrison; Karena Volesky; Rachel S. D. Lane (International Archives of Occupational and Environmental Health, 2023)
Objectives Exposure to ionizing radiation may increase the risk of circulatory diseases, including heart disease. A limited number of cohort studies of underground miners have investigated these associations. We previously reported a positive but non-statistically significant association between radon progeny and heart disease in a cohort of Newfoundland fluorspar miners. In this study, we report updated findings that incorporate 15 additional years of follow-up. Methods The cohort included 2050 miners who worked in the fluorspar mines from 1933 to 1978. Statistics Canada linked the personal identifying data of the miners to Canadian mortality data to identify deaths from 1950 to 2016. We used previously derived individual-level estimates of annual radon progeny exposure in working-level months. Cumulative exposure was categorized into quantiles. We estimated relative risks and their 95% confidence intervals using Poisson regression for deaths from circulatory, ischemic heart disease and acute myocardial infarction. Relative risks were adjusted for attained age, calendar year, and the average number of cigarettes smoked daily. Results Relative to the Newfoundland male population, the standardized mortality ratio for circulatory disease in this cohort was 0.82 (95% CI 0.74–0.91). Those in the highest quantile of cumulative radon progeny exposure had a relative risk of circulatory disease mortality of 1.03 (95% CI 0.76–1.40) compared to those in the lowest quantile. The corresponding estimates for ischemic disease and acute myocardial infarction were 0.99 (95% CI 0.66–1.48), and 1.39 (95% CI 0.84–2.30), respectively. Conclusions Our findings do not support the hypothesis that occupational exposure to radon progeny increases the risk of circulatory disease.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Region-Dependent Viscoelastic Properties of Human Brain Tissue Under Large Deformations - Sowmya N. Sundaresh; John D. Finan; Benjamin S. Elkin; Andrew V. Basilio; Guy M. McKhann; Barclay Morrison (Annals of Biomedical Engineering, 2022)

Development of a ddPCR assay for the detection of the Smoky Madtom (Noturus baileyi) from eDNA in stream water samples - Aaron W. Aunins; Michael S. Eackles; Paul E. Super; Matt A. Kulp; Becky J. Nichols; Barbara A. Lubinski; Cheryl L. Morrison; Tim L. King (Conservation Genetics Resources, 2022)
The Smoky Madtom Noturus baileyi is a federally endangered species, whose native distribution includes lower Abrams Creek in Great Smoky Mountains National Park (GRSM) and Citico Creek in nearby Cherokee National Forest. Due to challenges for bio-monitoring posed by its nocturnality and cryptic life history, an environmental DNA (eDNA)-based approach for detection would be useful to complement existing electrofishing and seining efforts to better understand the distribution of this species. We developed a probe-based droplet digital PCR (ddPCR) assay to detect Smoky Madtoms from non-invasively collected water samples. The assay was specific to N. baileyi and did not amplify concentrated genomic DNA of 16 co-occurring or regional fish species, including the yellowfin madtom N. flavipinnis and stonecat N. flavus . The assay limit of detection (LOD) was determined to be 4.18 copies (95% CI: 3.95, 4.41). Several 2 L water samples collected from throughout various streams in GRSM in 2016 and 2017 were tested for the presence of N. baileyi using the ddPCR assay. N. baileyi was detected at two different sites in 2016 and 2017 within Abrams Creek previously known to contain N. baileyi , but no novel detections in other sampled streams were observed. This assay should prove useful for continued surveys of N. baileyi in GRSM.

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Quantifying the probability of detection of wild ungulates with the Judas technique - David S. L. Ramsey; Karl J. Campbell; Christian Lavoie; Norm Macdonald; Scott A. Morrison (Conservation Biology, 2022)
The Judas technique is often used in control or eradication of particular vertebrate pests. The technique exploits the tendency of individuals to form social groups. A radio collar is affixed to an individual and its subsequent monitoring facilitates the detection of other conspecifics. Efficacy of this technique would be improved if managers could estimate the probability that a Judas individual would detect conspecifics. To calculate this probability, we estimated association rates of Judas individuals with other Judas individuals, given the length of time the Judas has been deployed. We developed a simple model of space‐use for individual Judas animals and constrained detection probabilities to those specific areas. We then combined estimates for individual Judas animals to infer the probability that a wild individual could be detected in an area of interest via Judas surveillance. We illustrated the method by using data from a feral goat eradication program on Isla Santiago, Galápagos, and a feral pig eradication program on Santa Cruz Island, California. Association probabilities declined as the proximity between individual areas of use of a Judas pair decreased. Unconditional probabilities of detection within individual areas of use averaged 0.09 per month for feral pigs and 0.11 per month for feral goats. Probabilities that eradication had been achieved, given no detections of wild conspecifics, and an uninformative prior probability of eradication were 0.79 (90% CI 0.22–0.99) for feral goats and 0.87 (90% CI 0.44–1.0) for feral pigs. We envisage several additions to the analyses used that could improve estimates of Judas detection probability. Analyses such as these can help managers increase the efficacy of eradication efforts, leading to more effective effects to restore native biodiversity.

Unbound Brain-to-Plasma Partition Coefficient, Kp,uu,brain—a Game Changing Parameter for CNS Drug Discovery and Development - Irena Loryan; Andreas Reichel; Bo Feng; Christoffer Bundgaard; Christopher Shaffer; Cory Kalvass; Dallas Bednarczyk; Denise Morrison; Dominique Lesuisse; Edmund Hoppe; Georg C. Terstappen; Holger Fischer; et al. (Pharmaceutical Research, 2022)
Purpose More than 15 years have passed since the first description of the unbound brain-to-plasma partition coefficient (K p,uu,brain ) by Prof. Margareta Hammarlund-Udenaes, which was enabled by advancements in experimental methodologies including cerebral microdialysis. Since then, growing knowledge and data continue to support the notion that the unbound (free) concentration of a drug at the site of action, such as the brain, is the driving force for pharmacological responses. Towards this end, K p,uu,brain is the key parameter to obtain unbound brain concentrations from unbound plasma concentrations. Methods To understand the importance and impact of the K p,uu,brain concept in contemporary drug discovery and development, a survey has been conducted amongst major pharmaceutical companies based in Europe and the USA. Here, we present the results from this survey which consisted of 47 questions addressing: 1) Background information of the companies, 2) Implementation, 3) Application areas, 4) Methodology, 5) Impact and 6) Future perspectives. Results and conclusions From the responses, it is clear that the majority of the companies (93%) has established a common understanding across disciplines of the concept and utility of K p,uu,brain as compared to other parameters related to brain exposure. Adoption of the K p,uu,brain concept has been mainly driven by individual scientists advocating its application in the various companies rather than by a top-down approach. Remarkably, 79% of all responders describe the portfolio impact of K p,uu,brain implementation in their companies as ‘game-changing’. Although most companies (74%) consider the current toolbox for K p,uu,brain assessment and its validation satisfactory for drug discovery and early development, areas of improvement and future research to better understand human brain pharmacokinetics/pharmacodynamics translation have been identified.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Mismatch‐induced growth reductions in a clade of Arctic‐breeding shorebirds are rarely mitigated by increasing temperatures - Thomas K. Lameris; Pavel S. Tomkovich; James A. Johnson; R. I. Guy Morrison; Ingrid Tulp; Simeon Lisovski; Lucas DeCicco; Maksim Dementyev; Robert E. Gill; Job ten Horn; Theunis Piersma; Zachary Pohlen; et al. (Global Change Biology, 2022)
In seasonal environments subject to climate change, organisms typically show phenological changes. As these changes are usually stronger in organisms at lower trophic levels than those at higher trophic levels, mismatches between consumers and their prey may occur during the consumers’ reproduction period. While in some species a trophic mismatch induces reductions in offspring growth, this is not always the case. This variation may be caused by the relative strength of the mismatch, or by mitigating factors like increased temperature‐reducing energetic costs. We investigated the response of chick growth rate to arthropod abundance and temperature for six populations of ecologically similar shorebirds breeding in the Arctic and sub‐Arctic (four subspecies of Red Knot Calidris canutus , Great Knot C . tenuirostris and Surfbird C . virgata ). In general, chicks experienced growth benefits (measured as a condition index) when hatching before the seasonal peak in arthropod abundance, and growth reductions when hatching after the peak. The moment in the season at which growth reductions occurred varied between populations, likely depending on whether food was limiting growth before or after the peak. Higher temperatures led to faster growth on average, but could only compensate for increasing trophic mismatch for the population experiencing the coldest conditions. We did not find changes in the timing of peaks in arthropod availability across the study years, possibly because our series of observations was relatively short; timing of hatching displayed no change over the years either. Our results suggest that a trend in trophic mismatches may not yet be evident; however, we show Arctic‐breeding shorebirds to be vulnerable to this phenomenon and vulnerability to depend on seasonal prey dynamics.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate Change Implications for Tidal Marshes and Food Web Linkages to Estuarine and Coastal Nekton - Denise D. Colombano; Steven Y. Litvin; Shelby L. Ziegler; Scott B. Alford; Ronald Baker; Myriam A. Barbeau; Just Cebrián; Rod M. Connolly; Carolyn A. Currin; Linda A. Deegan; Justin S. Lesser; Charles W. Martin; et al. (Estuaries and Coasts, 2021)
Climate change is altering naturally fluctuating environmental conditions in coastal and estuarine ecosystems across the globe. Departures from long-term averages and ranges of environmental variables are increasingly being observed as directional changes [e.g., rising sea levels, sea surface temperatures (SST)] and less predictable periodic cycles (e.g., Atlantic or Pacific decadal oscillations) and extremes (e.g., coastal flooding, marine heatwaves). Quantifying the short- and long-term impacts of climate change on tidal marsh seascape structure and function for nekton is a critical step toward fisheries conservation and management. The multiple stressor framework provides a promising approach for advancing integrative, cross-disciplinary research on tidal marshes and food web dynamics. It can be used to quantify climate change effects on and interactions between coastal oceans (e.g., SST, ocean currents, waves) and watersheds (e.g., precipitation, river flows), tidal marsh geomorphology (e.g., vegetation structure, elevation capital, sedimentation), and estuarine and coastal nekton (e.g., species distributions, life history adaptations, predator-prey dynamics). However, disentangling the cumulative impacts of multiple interacting stressors on tidal marshes, whether the effects are additive, synergistic, or antagonistic, and the time scales at which they occur, poses a significant research challenge. This perspective highlights the key physical and ecological processes affecting tidal marshes, with an emphasis on the trophic linkages between marsh production and estuarine and coastal nekton, recommended for consideration in future climate change studies. Such studies are urgently needed to understand climate change effects on tidal marshes now and into the future.

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Identifying predictors of international fisheries conflict - Jessica Spijkers; Gerald G. Singh; Colette C. C. Wabnitz; Henrik Österblom; Graeme S. Cumming; Tiffany H. Morrison (Fish and Fisheries, 2021)
Marine capture fishery resources are declining, and demand for them is rising. These trends are suspected to incite conflict, but their effects have not been quantitatively examined. We applied a multi‐model ensemble approach to a global database of international fishery conflicts between 1974 and 2016 to test the supply‐induced scarcity hypothesis (diminishing supplies of fishery resources increase fisheries conflict), the demand‐induced scarcity hypothesis (rising demand for fishery resources increases fisheries conflict), and three alternative political and economic hypotheses. While no single indicator was able to fully explain international conflict over fishery resources, we found a positive relationship between increased conflict over fishery resources and higher levels of per capita GDP for the period 1975–1996. For the period 1997–2016, we found evidence supporting the demand‐induced scarcity hypothesis, and the notion that an increase in supply of fishery resources is linked to an increase in conflict occurrence. By identifying significant predictors of international fisheries conflict, our analysis provides useful information for policy approaches for conflict anticipation and management.

Assessing repellency, movement, and mortality of three species of stored product insects after exposure to deltamethrin-incorporated long-lasting polyethylene netting - D. S. Scheff; A. R. Gerken; W. R. Morrison; J. F. Campbell; F. H. Arthur; K. Y. Zhu (Journal of Pest Science, 2021)

Temporary threshold shift after noise exposure in hypobaric hypoxia at high altitude: results of the ADEMED expedition 2011 - K. Fehrenbacher; C. Apel; D. Bertsch; M. S. van der Giet; S. van der Giet; M. Grass; C. Gschwandtl; N. Heussen; N. Hundt; C. Kühn; A. Morrison; M. Müller-Ost; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives To evaluate whether there is an increased risk for noise-induced hearing loss at high altitude rsp. in hypobaric hypoxia. Methods Thirteen volunteers got standard audiometry at 125, 250, 500, 750, 1000, 1500, 2000, 3000, 4000, 6000, and 8000 Hz before and after 10 min of white noise at 90 dB. The system was calibrated for the respective altitude. Measurements were performed at Kathmandu (1400 m) and at Gorak Shep (5300 m) (Solo Khumbu/Nepal) after 10 days of acclimatization while on trek. Temporary threshold shift (TTS) was analyzed by descriptive statistics and by factor analysis. Results TTS is significantly more pronounced at high altitudes. Acclimatization does not provide any protection of the inner ear, although it increases arterial oxygen saturation. Conclusion The thresholds beyond which noise protection is recommended (> 80 dB) or necessary (> 85 dB) are not sufficient at high altitudes. We suggest providing protective devices above an altitude of 1500 m (“ear threshold altitude”) when noise level is higher than 75 dB and using them definitively above 80 dB. This takes the individual reaction on hypobaric hypoxia at high altitude into account.

Export of photolabile and photoprimable dissolved organic carbon from the Connecticut River - Byungman Yoon; Jacob D. Hosen; Ethan D. Kyzivat; Jennifer H. Fair; Lisa C. Weber; Kelly S. Aho; Rachel Lowenthal; Serena Matt; William V. Sobczak; Jamie B. Shanley; Jon Morrison; James E. Saiers; et al. (Aquatic Sciences, 2021)

Effects of temperature on sexual development in steelhead, Oncorhynchus mykiss - Kathleen S. Cole; David L. G. Noakes; Neil Thompson; Michael Blouin; Bruce Morrison; Ryan B. Couture; Joseph O’Neil; Carl B. Schreck (Environmental Biology of Fishes, 2021)

Source Switching Maintains Dissolved Organic Matter Chemostasis Across Discharge Levels in a Large Temperate River Network - J. D. Hosen; K. S. Aho; J. H. Fair; E. D. Kyzivat; S. Matt; J. Morrison; A. Stubbins; L. C. Weber; B. Yoon; P. A. Raymond (Ecosystems, 2021)

Antisense Oligonucleotide Therapy Targeted Against ATXN3 Improves Potassium Channel–Mediated Purkinje Neuron Dysfunction in Spinocerebellar Ataxia Type 3 - David D. Bushart; Annie J. Zalon; Hongjiu Zhang; Logan M. Morrison; Yuanfang Guan; Henry L. Paulson; Vikram G. Shakkottai; Hayley S. McLoughlin (The Cerebellum, 2021)

Seawater transmission and infection dynamics of pilchard orthomyxovirus (POMV) in Atlantic salmon ( Salmo salar ) - Francisca Samsing; Megan Rigby; Hedda K. Tengesdal; Richard S. Taylor; Daniela Farias; Richard N. Morrison; Scott Godwin; Carla Giles; Jeremy Carson; Chloe J. English; Roger Chong; James W. Wynne (Journal of Fish Diseases, 2021)
The Tasmanian salmon industry had remained relatively free of major viral diseases until the emergence of pilchard orthomyxovirus (POMV). Originally isolated from wild pilchards, POMV is of concern to the industry as it can cause high mortality in farmed salmon ( Salmo salar ). Field observations suggest the virus can spread from pen to pen and between farms, but evidence of passive transmission in sea water was unclear. Our aim was to establish whether direct contact between infected and naïve fish was required for transmission, and to examine viral infection dynamics. Atlantic salmon post‐smolts were challenged with POMV by either direct exposure via cohabitation or indirect exposure via virus‐contaminated sea water. POMV was transmissible in sea water and direct contact between fish was not required for infection. Head kidney and heart presented the highest viral loads in early stages of infection. POMV survivors presented low viral loads in most tissues, but these remained relatively high in gills. A consistent feature was the infiltration of viral‐infected melanomacrophages in different tissues, suggesting an important role of these in the immune response to POMV. Understanding POMV transmission and host–pathogen interactions is key for the development of improved surveillance tools, transmission models and ultimately for disease prevention.

Infanticide and partial cannibalism in free-ranging Coquerel’s sifaka (Propithecus coquereli) - Malcolm S. Ramsay; Benjamin Morrison; Samantha M. Stead (Primates, 2020)

Quantifying student engagement in learning about climate change using galvanic hand sensors in a controlled educational setting - A. L. Morrison; S. Rozak; A. U. Gold; J. E. Kay (Climatic Change, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Merlin modulates process outgrowth and synaptogenesis in the cerebellum - A. Toledo; F. Lang; M. Doengi; H. Morrison; V. Stein; S. L. Baader (Brain Structure and Function, 2019)

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Differential Proteomics for Distinguishing Ischemic Stroke from Controls: a Pilot Study of the SpecTRA Project - A. M. Penn; V. Saly; A. Trivedi; M. L. Lesperance; K. Votova; A. M. Jackson; N.S. Croteau; R. F. Balshaw; M. B. Bibok; D. S. Smith; K. K. Lam; J. Morrison; et al. (Translational Stroke Research, 2018)

Marine fisheries and future ocean conflict - Jessica Spijkers; Tiffany H Morrison; Robert Blasiak; Graeme S Cumming; Matthew Osborne; James Watson; Henrik Österblom (Fish and Fisheries, 2018)
Conflict over marine fishery resources is a growing security concern. Experts expect that global changes in our climate, food systems and oceans may spark or exacerbate resource conflicts. An initial scan of 803 relevant papers and subsequent intensive review of 31 fisheries conflict studies, focused on subnational and international conflicts, suggests that four substantial scientific gaps need addressing to improve our understanding of the nature and drivers of fisheries conflict. First, fisheries conflict and levels of conflict intensity are not precisely defined. Second, complex adaptive systems thinking is underutilized but has the potential to produce more realistic causal models of fishery conflict. Third, comparative large‐scale data and suitably integrative methodologies are lacking, underscoring the need for a standardized and comparable database of fisheries conflict cases to aid extrapolation beyond single case‐studies. Fourth, there is room for a more widespread application of higher order concepts and associated terminology. Importantly, the four gaps highlight the homogenized nature of current methodological and theoretical approaches to understanding fishery conflict, which potentially presents us with an oversimplified understanding of these conflicts. A more nuanced understanding of the complex and dynamic nature of fishery conflict and its causes is not only scientifically critical, but increasingly relevant for policymakers and practitioners in this turbulent world.

Enhanced hemoglobin–oxygen unloading in migratory salmonids - Jacelyn J. Shu; Till S. Harter; Phillip R. Morrison; Colin J. Brauner (Journal of Comparative Physiology B, 2018)

Species associations overwhelm abiotic conditions to dictate the structure and function of wood‐decay fungal communities - Daniel S. Maynard; Kristofer R. Covey; Thomas W. Crowther; Noah W. Sokol; Eric W. Morrison; Serita D. Frey; Linda T. A. van Diepen; Mark A. Bradford (Ecology, 2018)
Environmental conditions exert strong controls on the activity of saprotrophic microbes, yet abiotic factors often fail to adequately predict wood decomposition rates across broad spatial scales. Given that species interactions can have significant positive and negative effects on wood‐decay fungal activity, one possibility is that biotic processes serve as the primary controls on community function, with abiotic controls emerging only after species associations are accounted for. Here we explore this hypothesis in a factorial field warming‐ and nitrogen‐addition experiment by examining relationships among wood decomposition rates, fungal activity, and fungal community structure. We show that functional outcomes and community structure are largely unrelated to abiotic conditions, with microsite and plot‐level abiotic variables explaining at most 19% of the total variability in decomposition and fungal activity, and 2% of the variability in richness and evenness. In contrast, taxonomic richness, evenness, and species associations (i.e., co‐occurrence patterns) exhibited strong relationships with community function, accounting for 52% of the variation in decomposition rates and 73% in fungal activity. A greater proportion of positive vs. negative species associations in a community was linked to strong declines in decomposition rates and richness. Evenness emerged as a key mediator between richness and function, with highly even communities exhibiting a positive richness–function relationship and uneven communities exhibiting a negative or null response. These results suggest that community‐assembly processes and species interactions are important controls on the function of wood‐decay fungal communities, ultimately overwhelming substantial differences in abiotic conditions.

Daily land use regression estimated woodsmoke and traffic pollution concentrations and the triggering of ST-elevation myocardial infarction: a case-crossover study - David Q. Rich; Mark J. Utell; Daniel P. Croft; Sally W. Thurston; Kelly Thevenet-Morrison; Kristin A. Evans; Frederick S. Ling; Yilin Tian; Philip K. Hopke (Air Quality, Atmosphere & Health, 2018)

Transcriptome profiles of sunflower reveal the potential role of microsatellites in gene expression divergence - Chathurani Ranathunge; Gregory L. Wheeler; Melody E. Chimahusky; Meaghan M. Kennedy; Jesse I. Morrison; Brian S. Baldwin; Andy D. Perkins; Mark E. Welch (Molecular Ecology, 2018)
The mechanisms by which natural populations generate adaptive genetic variation are not well understood. Some studies propose that microsatellites can function as drivers of adaptive variation. Here, we tested a potentially adaptive role for transcribed microsatellites with natural populations of the common sunflower ( Helianthus annuus L.) by assessing the enrichment of microsatellites in genes that show expression divergence across latitudes. Seeds collected from six populations at two distinct latitudes in Kansas and Oklahoma were planted and grown in a common garden. Morphological measurements from the common garden demonstrated that phenotypic variation among populations is largely explained by underlying genetic variation. An RNA‐Seq experiment was conducted with 96 of the individuals grown in the common garden and differentially expressed (DE) transcripts between the two latitudes were identified. A total number of 825 DE transcripts were identified. DE transcripts and nondifferentially expressed (NDE) transcripts were then scanned for microsatellites. The abundance of different motif lengths and types in both groups were estimated. Our results indicate that DE transcripts are significantly enriched with mononucleotide repeats and significantly depauperate in trinucleotide repeats. Further, the standardized mononucleotide repeat motif A and dinucleotide repeat motif AG were significantly enriched within DE transcripts while motif types, C, AT, ACC and AAC in DE transcripts, are significantly differentiated in microsatellite tract length between the two latitudes. The tract length differentiation at specific microsatellite motif types across latitudes and their enrichment within DE transcripts indicate a potential functional role for transcribed microsatellites in gene expression divergence in sunflower.

Commentary: Why Pharmaceutical Scientists in Early Drug Discovery Are Critical for Influencing the Design and Selection of Optimal Drug Candidates - Margaret S. Landis; Shobha Bhattachar; Mehran Yazdanian; John Morrison (AAPS PharmSciTech, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Medical Knowledge Assessment by Hematology and Medical Oncology In-Training Examinations Are Better Than Program Director Assessments at Predicting Subspecialty Certification Examination Performance - Frances A. Collichio; Brian J. Hess; Elaine A. Muchmore; Lauren Duhigg; Rebecca S. Lipner; Steven Haist; Janine L. Hawley; Carol A. Morrison; Charles P. Clayton; Marilyn J. Raymond; Karen M. Kayoumi; Scott D. Gitlin (Journal of Cancer Education, 2017)

New Directions for Understanding the Spatial Resilience of Social–Ecological Systems - Graeme S. Cumming; Tiffany H. Morrison; Terence P. Hughes (Ecosystems, 2017)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Differences in carbon source utilisation by orchid mycorrhizal fungi from common and endangered species of Caladenia (Orchidaceae) - S. Mehra; P. D. Morrison; F. Coates; A. C. Lawrie (Mycorrhiza, 2017)

Three-dimensional assessment of postural tremor during goal-directed aiming - K. J. Kelleran; S. Morrison; D. M. Russell (Experimental Brain Research, 2016)

Optimising gut colonisation resistance against Clostridium difficile infection - S. Yuille; W. G. Mackay; D. J. Morrison; M. C. Tedford (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Evaluating the efficacy of bioremediating a diesel-contaminated soil using ecotoxicological and bacterial community indices - Leadin Salah Khudur; Esmaeil Shahsavari; Ana F. Miranda; Paul D. Morrison; Dayanthi Nugegoda; Andrew S. Ball (Environmental Science and Pollution Research, 2015)

Anterior–posterior dissociation of the default mode network in dogs - Sreenath P. Kyathanahally; Hao Jia; Oleg M. Pustovyy; Paul Waggoner; Ronald Beyers; John Schumacher; Jay Barrett; Edward E. Morrison; Nouha Salibi; Thomas S. Denney; Vitaly J. Vodyanoy; Gopikrishna Deshpande (Brain Structure and Function, 2015)

Site-specific pre-evaluation of bioremediation technologies for chloroethene degradation - S. S. Patil; E. M. Adetutu; P. J. Sheppard; P. Morrison; I. R. Menz; A. S. Ball (International Journal of Environmental Science and Technology, 2014)

Assessing the hydrocarbon degrading potential of indigenous bacteria isolated from crude oil tank bottom sludge and hydrocarbon-contaminated soil of Azzawiya oil refinery, Libya - Abdulatif A. Mansur; Eric M. Adetutu; Krishna K. Kadali; Paul D. Morrison; Yuana Nurulita; Andrew S. Ball (Environmental Science and Pollution Research, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

An initial assessment of spatial relationships between respiratory cases, soil metal content, air quality and deprivation indicators in Glasgow, Scotland, UK: relevance to the environmental justice agenda - S. Morrison; F. M. Fordyce; E. Marian Scott (Environmental Geochemistry and Health, 2014)

Evaluation of wireless sensor networks (WSNs) for remote wetland monitoring: design and initial results - Carl J. Watras; Michael Morrow; Ken Morrison; Sean Scannell; Steve Yaziciaglu; Jordan S. Read; Yu-Hen Hu; Paul C. Hanson; Tim Kratz (Environmental Monitoring and Assessment, 2014)

Sensory and Physicochemical Properties of Smoked Catfish Sausages - Sovann Kin; Rebecca Morrison; Ana Claudia Tolentino; Alessandra J. Pham; Brian S. Smith; Taejo Kim; Juan L. Silva; M. Wes Schilling (Journal of Aquatic Food Product Technology, 2013)

Winter weather versus group thermoregulation: what determines survival in hibernating mammals? - V. P. Patil; S. F. Morrison; T. J. Karels; D. S. Hik (Oecologia, 2013)

Molecular investigation of bacterial communities on the inner and outer surfaces of peripheral venous catheters - L. Zhang; M. Morrison; G. R. Nimmo; K. S. Sriprakash; S. Mondot; J. R. Gowardman; N. George; N. Marsh; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Use of A tlantic salmon, S almo salar L., farm treatment data and bioassays to assess for resistance of sea lice, L epeophtheirus salmonis , to emamectin benzoate ( SLICE ® ) in B ritish C olumbia, C anada - S M Saksida; D Morrison; P McKenzie; B Milligan; E Downey; B Boyce; A Eaves (Journal of Fish Diseases, 2013)

Changes in postural sway as a function of prolonged walking - Kathleen S. Thomas; Bonnie L. VanLunen; Steven Morrison (European Journal of Applied Physiology, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

Erratum to: Viscoelastic Properties of the Rat Brain in the Sagittal Plane: Effects of Anatomical Structure and Age - John D. Finan; Benjamin S. Elkin; Erica M. Pearson; Irene L. Kalbian; Barclay Morrison (Annals of Biomedical Engineering, 2012)

Viscoelastic Properties of the Rat Brain in the Sagittal Plane: Effects of Anatomical Structure and Age - John D. Finan; Benjamin S. Elkin; Erica M. Pearson; Irene L. Kalbian; Barclay Morrison (Annals of Biomedical Engineering, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Expression of Histone Deacetylases in Cellular Compartments of the Mouse Brain and the Effects of Ischemia - Selva Baltan; Amelia Bachleda; Richard S. Morrison; Sean P. Murphy (Translational Stroke Research, 2011)

Similarity in the dynamics of contralateral motor overflow through increasing frequency of movement in a single limb - S. Morrison; S. L. Hong; K. M. Newell (Experimental Brain Research, 2011)

Genetic discontinuity among regional populations of Lophelia pertusa in the North Atlantic Ocean - Cheryl L. Morrison; Steve W. Ross; Martha S. Nizinski; Sandra Brooke; Johanna Järnegren; Rhian G. Waller; Robin L. Johnson; Tim L. King (Conservation Genetics, 2011)

Detection of sub-tidal mussel beds on rocky reefs using acoustics - M. A. Morrison; A. G. Jeffs; S. H. Hooker (International Journal of Remote Sensing, 2010)

The efficacy of emamectin benzoate against infestations of sea lice, Lepeophtheirus salmonis , on farmed Atlantic salmon, Salmo salar L., in British Columbia - S M Saksida; D Morrison; C W Revie (Journal of Fish Diseases, 2010)

The skin as a social organ - India Morrison; Line S. Löken; Håkan Olausson (Experimental Brain Research, 2010)

Addition of individual chromosomes of maize inbreds B73 and Mo17 to oat cultivars Starter and Sun II: maize chromosome retention, transmission, and plant phenotype - Howard W. Rines; Ronald L. Phillips; Ralf G. Kynast; Ron J. Okagaki; Mark W. Galatowitsch; Paul A. Huettl; Adrian O. Stec; Morrison S. Jacobs; Jayanti Suresh; Hedera L. Porter; Matthew D. Walch; Candida B. Cabral (Theoretical and Applied Genetics, 2009)

An Efficient RNA Extraction Method for Estimating Gut Microbial Diversity by Polymerase Chain Reaction - Seungha Kang; Stuart E. Denman; Mark Morrison; Zhongtang Yu; Chris S. McSweeney (Current Microbiology, 2009)

Quantifying Eradication Success: the Removal of Feral Pigs from Santa Cruz Island, California - DAVID S. L. RAMSEY; JOHN PARKES; SCOTT A. MORRISON (Conservation Biology, 2009)
A major challenge facing pest‐eradication efforts is determining when eradication has been achieved. When the pest can no longer be detected, managers have to decide whether the pest has actually been eliminated and hence to decide when to terminate the eradication program. For most eradication programs, this decision entails considerable risk and is the largest single issue facing managers of such programs. We addressed this issue for an eradication program of feral pigs ( Sus scrofa ) from Santa Cruz Island, California. Using a Bayesian approach, we estimated the degree of confidence in the success of the eradication program at the point when monitoring failed to detect any more pigs. Catch‐effort modeling of the hunting effort required to dispatch pigs during the eradication program was used to determine the relationship between detection probability and searching effort for different hunting methods. We then used these relationships to estimate the amount of monitoring effort required to declare eradication successful with criteria that either set a threshold for the probability that pigs remained undetected (type I error) or minimized the net expected costs of the eradication program (cost of type I and II errors). For aerial and ground‐based monitoring techniques, the amount of search effort required to declare eradication successful on the basis of either criterion was highly dependent on the prior belief in the success of the program unless monitoring intensities exceeded 30 km of searching effort per square kilometer of search area for aerial monitoring and, equivalently, 38 km for ground monitoring. Calculation of these criteria to gauge the success of eradication should form an essential component of any eradication program as it allows for a transparent assessment of the risks inherent in the decision to terminate the program.

Influence of food hoarding behavior on the over-winter survival of pikas in strongly seasonal environments - Shawn F. Morrison; Graeme Pelchat; Aaron Donahue; David S. Hik (Oecologia, 2009)

Nitrogen enrichment modifies plant community structure via changes to plant–soil feedback - P. Manning; S. A. Morrison; M. Bonkowski; R. D. Bardgett (Oecologia, 2008)

Co‐occurrence of β‐ N ‐methylamino‐ l ‐alanine, a neurotoxic amino acid with other cyanobacterial toxins in British waterbodies, 1990–2004 - James S. Metcalf; Sandra Anne Banack; Jaime Lindsay; Louise F. Morrison; Paul Alan Cox; Geoffrey A. Codd (Environmental Microbiology, 2008)
Summary The neurotoxic amino acid, β‐ N ‐methylamino‐ l ‐alanine, was found to be present in all of 12 analysed samples of cyanobacterial blooms, scums and mats, which had been collected in seven years between 1990 and 2004 inclusive and stored at −20°C. BMAA identification was by high performance liquid chromatography with fluorescence detection and by triple quadrapole mass spectrometry after derivatization. The samples originated from 11 freshwater lakes and 1 brackish waterbody, used either for drinking water, recreation, or both. BMAA was present at between 8 and 287 μg g −1 cyanobacterial dry weight and was present as both the free amino acid and associated with precipitated proteins. Ten of the samples contained additional cyanotoxins (including microcystins, anatoxin‐a, nodularin and saxitoxin) at the time of sample collection. Five of the samples were associated with animal deaths, attributable at the time of sample collection, to microcystins, nodularin or anatoxin‐a. The data demonstrate the presence of BMAA by high performance liquid chromatography and mass spectrometry in a diverse range of cyanobacterial bloom samples from high resource waterbodies. Furthermore, samples collected over several years shows that BMAA can co‐occur with other known cyanotoxins in such waterbodies. Health risk assessment of cyanobacterial BMAA in waterbodies is suggested.

The Glial Response to CNS HIV Infection Includes p53 Activation and Increased Expression of p53 Target Genes - Suman Jayadev; Bomy Yun; Huy Nguyen; Hideaki Yokoo; Richard S. Morrison; Gwenn A. Garden (Journal of Neuroimmune Pharmacology, 2007)

Inverse relations in the patterns of muscle and center of pressure dynamics during standing still and movement postures - S. Morrison; S. L. Hong; K. M. Newell (Experimental Brain Research, 2007)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The effects of age and streptozotocin diabetes on the sympathetic innervation in the rat penis - J. F. B. Morrison; D. J. Pallot; R. Sheen; S. Dhanasekaran; E. P. K. Mensah-Brown (Molecular and Cellular Biochemistry, 2007)

Comprehensive genetic analyses reveal evolutionary distinction of a mouse ( Zapus hudsonius preblei ) proposed for delisting from the US Endangered Species Act - TIM L. KING; JOHN F. SWITZER; CHERYL L. MORRISON; MICHAEL S. EACKLES; COLLEEN C. YOUNG; BARBARA A. LUBINSKI; PAUL CRYAN (Molecular Ecology, 2006)
Zapus hudsonius preblei , listed as threatened under the US Endangered Species Act (ESA), is one of 12 recognized subspecies of meadow jumping mice found in North America. Recent morphometric and phylogenetic comparisons among Z. h. preblei and neighbouring conspecifics questioned the taxonomic status of selected subspecies, resulting in a proposal to delist the Z. h. preblei from the ESA. We present additional analyses of the phylogeographic structure within Z. hudsonius that calls into question previously published data (and conclusions) and confirms the original taxonomic designations. A survey of 21 microsatellite DNA loci and 1380 base pairs from two mitochondrial DNA (mtDNA) regions (control region and cytochrome b ) revealed that each Z. hudsonius subspecies is genetically distinct. These data do not support the null hypothesis of a homogeneous gene pool among the five subspecies found within the southwestern portion of the species’ range. The magnitude of the observed differentiation was considerable and supported by significant findings for nearly every statistical comparison made, regardless of the genome or the taxa under consideration. Structuring of nuclear multilocus genotypes and subspecies‐specific mtDNA haplotypes corresponded directly with the disjunct distributions of the subspecies investigated. Given the level of correspondence between the observed genetic population structure and previously proposed taxonomic classification of subspecies (based on the geographic separation and surveys of morphological variation), we conclude that the nominal subspecies surveyed in this study do not warrant synonymy, as has been proposed for Z. h. preblei , Z. h. campestris , and Z. h. intermedius .

In vitro interactions between Neoparamoeba spp. and salmonid leucocytes; the effect of parasite sonicate on anterior kidney leucocyte function - K. Gross; S. Alcorn; A. Murray; R. Morrison; B. Nowak (Journal of Fish Biology, 2006)
Sonicated Neoparamoeba spp. (Nspp) did not affect the in vitro respiratory burst response of leucocytes isolated from Atlantic salmon Salmo salar , rainbow trout Oncorhynchus mykiss and chinook salmon Oncorhynchus tshawytscha anterior kidneys ( P > 0·05). Atlantic salmon and chinook salmon leucocytes pre‐incubated with the parasites, however, responded to phorbol myristate acetate (PMA) stimulation with a greater response compared to cells incubated with PMA on its own ( P

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Age-related differences in inter-digit coupling during finger pinching - Justin Keogh; S. Morrison; R. Barrett (European Journal of Applied Physiology, 2006)

The effects of unilateral muscle fatigue on bilateral physiological tremor - S. Morrison; J. Kavanagh; S. J. Obst; J. Irwin; L. J. Haseler (Experimental Brain Research, 2005)

Coordination of head and trunk accelerations during walking - J. J. Kavanagh; S. Morrison; R. S. Barrett (European Journal of Applied Physiology, 2005)

Geodetic sensitivity to surface meteorological data: 24-h and 6-h observing sessions - J. Ray; M. Morrison; S. Hilla; W. Dillinger; G. Mader (GPS Solutions, 2005)

Combined effects of selected Penicillium mycotoxins on in vitro proliferation of porcine lymphocytes - Aksel Bernhoft; Modestas Keblys; Ellen Morrison; Hans Jørgen S. Larsen; Arne Flåøyen (Mycopathologia, 2004)

Augmented visual feedback increases finger tremor during postural pointing - J. Keogh; S. Morrison; R. Barrett (Experimental Brain Research, 2004)

The effects of the Penicillium mycotoxins citrinin, cyclopiazonic acid, ochratoxin A, patulin, penicillic acid, and roquefortine C on in vitro proliferation of porcine lymphocytes - Modestas Keblys; Aksel Bernhoft; Constance C. Höfer; Ellen Morrison; Hans Jørgen S. Larsen; Arne Flåøyen (Mycopathologia, 2004)

Short-Term Toxicity and Binding of Platinum to Freshwater Periphyton Communities - S. Rauch; M. Paulsson; M. Wilewska; H. Blanck; G. M. Morrison (Archives of Environmental Contamination and Toxicology, 2004)

Comparative Tissue Distribution of Metals in Birds in Sweden Using ICP-MS and Laser Ablation ICP-MS - Kristine H. Ek; Gregory M. Morrison; Peter Lindberg; Sbastien Rauch (Archives of Environmental Contamination and Toxicology, 2004)

Effects of age and streptozotocin-induced diabetes on biogenic amines in rat tail artery - J.F.B. Morrison; S. Dhanasekaran; R. Sheen (Molecular and Cellular Biochemistry, 2004)

Passive hyperthermia reduces voluntary activation and isometric force production - Shawnda Morrison; Gordon G. Sleivert; Stephen S. Cheung (European Journal of Applied Physiology, 2004)

Determination of Heavy Metal Concentrations and Metal Fingerprints of Sewage Sludge from Eastern Cape Province, South Africa by Inductively Coupled Plasma – Mass Spectrometry (ICP-MS) and Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS) - G. Morrison; O. S. Fatoki; S. Linder; C. Lundehn (Water, Air, & Soil Pollution, 2004)

Platinum Group Elements in the Feathers of Raptors and Their Prey - K. H. Jensen; S. Rauch; G. M. Morrison; P. Lindberg (Archives of Environmental Contamination and Toxicology, 2002)

Molecular determination of paternity in a natural population of the multiply mating polygynous lizard Eulamprus heatwolei - S. F. Morrison; J. Scott Keogh; I. A. W. Scott (Molecular Ecology, 2002)
We studied the mating system of the southern water skink, Eulamprus heatwolei , during spring and summer (encompassing the breeding season) in a population in southeastern Australia. We examined potential attributes that might influence the mating system and male reproductive success including home range size, physical proximity of adults and body size, and then genotyped all mothers, offspring and potential sires. Home range overlap of both sexes was extensive, with adult females sharing the greatest amount of space with each other and adult males the least amount of space with each other. However, not all adults hold home ranges. We classified approximately one quarter of adult males as home range holders and the rest as ‘floaters’. Adult females occupy home ranges more than males, with approximately three‐quarters classified as home range holders. Home range ownership is not correlated with body size for either sex, however, male body size is positively correlated with the number of adult female home ranges that his home range overlaps and adult male home ranges are larger than those of females. We used microsatellite genotyping to assign paternities to 55 offspring from 17 litters and then compared this data with our home range and behavioural observations. This species displays extreme levels of multiple paternity given the small mean clutch size of three. Multiple paternity was confirmed in 11 (64.7%) of 17 clutches but three other clutches (for a total of 82.4%) also may display multiple paternity. A total of 30 offspring from 12 litters were assigned to 10 of the 32 genotyped adult males from our study site. Of these 10 adult males, half were home range holders. Five complete clutches and a total of 25 out of the 55 offspring could not be positively assigned to any male surveyed as part of the study and were attributed to floater males or resident males adjacent to our study site that had not been genotyped. While sample sizes are small, neither male home range ownership nor body size is significantly correlated with the number of paternities a male obtained. Our study suggests a polygynous mating system for this species.

Marine Boundary-Layer Variability Over The Indian Ocean During Indoex (1998) - Vijayakumar Manghnani; Sethu Raman; Devdutta S. Niyogi; Vinayaka Parameswara; John M. Morrison; S. V. Ramana; J. V. S. S. Raju (Boundary-Layer Meteorology, 2000)

The Impact of Logging on Wildlife: A Study in Northeastern Pennsylvania - Todd S. Fredericksen; Brad D. Ross; Wayne Hoffman; Eric Ross; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson (Journal of Forestry, 2000)
Seeing and conserving wildlife are among the most important management objectives for nonindustrial private landowners in the eastern United States. Landowners want profitable timber harvests but also want to know how harvesting will affect their wildlife. The study examined associations between stand characteristics and wildlife abundance on 40 stands receiving different logging intensities in northeastern Pennsylvania and found that landowners have some choices when harvesting their stands for retaining or attracting different types of wildlife.

Variation in the number of expressed MHC genes in different cattle class I haplotypes - S. A. Ellis; E. C. Holmes; K. A. Staines; K. B. Smith; M. J. Stear; D. J. McKeever; N. D. MacHugh; W. I. Morrison (Immunogenetics, 1999)

Current and elevated levels of UV‐B radiation have few impacts on yields of perennial forage crops - Yousef A. Papadopoulos; Robert J. Gordon; Kenneth B. Mcrae; RoY. S. Bush; Gilles Bélanger; E. AnnE. Butler; Sherry A. E. Fillmore; Malcolm Morrison (Global Change Biology, 1999)
Summary Two experiments assessed the effect of current and elevated levels of ultraviolet B (UV‐B) radiation on forage crop production. The effect of current levels of UV‐B radiation was assessed by comparing the growth of eight cultivars of four legume and four grass species for three growing seasons (1994–96) under simulated sward conditions in the field. An exclusion system using cellulose diacetate or polyester covers provided comparable growing conditions for the plants, except for the presence or absence of ambient UV‐B radiation, respectively. The second experiment studied the effect of elevated levels of UV‐B on eight cultivars of two legume and two grass species in the greenhouse under simulated sward conditions. Natural lighting with sufficient supplemental light was used to provide ideal growing conditions for a 16‐h day length. Separate sets of UV lights were installed to provide UV‐B levels at approximately the same intensity as would be found in mid summer, and 33% and 66% more than this value. A fourth treatment consisted of removing UV‐B radiation by using a polyester filter. Plant production was measured in both experiments. In 1994, field herbage yields from all young grass and legume seedlings were not significantly affected by the exclusion of ambient UV‐B radiation, with the exception of alfalfa. Intra‐specific variations with alfalfa yields were found for reduced levels of UV‐B radiation. In general, these trends persisted as stands matured during two post seeding years. In the second experiment, no significant differences were observed for all tested species with increasing levels of UV‐B radiation, except with some alfalfa cultivars and one birdsfoot trefoil cultivar. Collectively, these results demonstrate that in the northern latitudes young and mature plants of the studied species are resistant to current and potentially higher levels of solar UV‐B radiation, with the exception of some alfalfa cultivars. The yield of these cultivars increased under enhanced levels of UV‐B radiation in the greenhouse and decreased when UV‐B was excluded in the field.

Litter decomposition rates in Canadian forests - T. R. Moore; J. A. Trofymow; B. Taylor; C. Prescott; C. Camiré; L. Duschene; J. Fyles; L. Kozak; M. Kranabetter; I. Morrison; M. Siltanen; S. Smith; et al. (Global Change Biology, 1999)
The effect of litter quality and climate on the rate of decomposition of plant tissues was examined by the measurement of mass remaining after 3 years’ exposure of 11 litter types placed at 18 forest sites across Canada. Amongst sites, mass remaining was strongly related to mean annual temperature and precipitation and amongst litter types the ratio of Klason lignin to nitrogen in the initial tissue was the most important litter quality variable. When combined into a multiple regression, mean annual temperature, mean annual precipitation and Klason lignin:nitrogen ratio explained 73% of the variance in mass remaining for all sites and tissues. Using three doubled CO 2 GCM climate change scenarios for four Canadian regions, these relationships were used to predict increases in decomposition rate of 4–7% of contemporary rates (based on mass remaining after 3 years), because of increased temperature and precipitation. This increase may be partially offset by evidence that plants growing under elevated atmospheric CO 2 concentrations produce litter with high lignin:nitrogen ratios which slows the rate of decomposition, but this change will be small compared to the increased rate of decomposition derived from climatic changes.

Biological and pharmacokinetic properties of a novel immunoglobulin-CD4 fusion protein - J. B. Lyczak; S. L. Morrison (Archives of Virology, 1994)

An immunological study of infection of hamsters with large and small plaque canine distemper viruses - S. L. Cosby; J. Morrison; B. K. Rima; S. J. Martin (Archives of Virology, 1983)

Evaluation of the mutagenic potential of bacterial polychlorinated biphenyl biodegradation products - G. S. Sayler; M. C. Reid; B. K. Perkins; R. M. Pagni; R. L. Smith; T. K. Rao; J. L. Epler; W. D. Morrison; R. DuFrain (Archives of Environmental Contamination and Toxicology, 1982)